A Five-Year Analysis of Antibiotic Resistance Trends among Bacteria Identified in Positive Urine Samples in a Tertiary Care Hospital from Bucharest, Romania - Alina Maria Borcan; Georgiana Radu; Mădălina Simoiu; Elena Liliana Costea; Alexandru Rafila (MDPI AG, 2024)
The rise of multidrug-resistant bacteria (MDR) has resulted in limited treatment options and poorer outcomes for patients. The objective of this study was to analyze the overall antibiotic resistance trends and distribution for pathogens identified in urine samples at the National Institute of Infectious Diseases "Prof. Dr. Matei Balș" from Bucharest, Romania, over a 5-year period. Antibiotic susceptibility testing was performed using automatic systems and the disk diffusion method. ESBL- and carbapenemases-producing strains were identified using immunochromatography tests, and ROSCO Diagnostica kits were used for definitive confirmation. All results were interpreted according to EUCAST clinical breakpoints. Gram-negative rods (GNR) had overall resistance rates higher than 50% for penicillin and 40% for 3rd- and 4th-generation cephalosporins. Escherichia coli resistance to fosfomycin (3%) and nitrofurantoin (2%) remains low, and 33.30% of E. coli, 48% of Klebsiella spp., and 37% of Pseudomonas aeruginosa isolates were multidrug-resistant (MDR). All Acinetobacter baumannii isolates were MDR by the last year of the study. For Gram-positive cocci (GPC), 37% of all Enterococcus faecium strains and 2% of Enterococcus faecalis were vancomycin-resistant (VRE). E. coli's incidence in UTIs' etiology is on a downward trend. The incidence of Klebsiella spp. and GPCs is rising. Antibiotic stewardship strategies should be implemented after carefully considering regional variations in etiology and resistance trends.